Interprofessional Education in Multiprofessional Residency Programs in Health in Brazil: An integrative review (Research, Society and Development, 2021)
This study aimed to analyze the current scenario of interprofessional education in Multiprofessional Residencies in Brazil, with regard to the challenges, operationalization strategies and impacts of collaborative practices in the work process of multiprofessional health teams. An integrative review of descriptive character and qualitative approach was carried out, based on the analysis of articles published between 2015 and 2020, in the Virtual Health Library. The results showed that interprofessional education faces several operationalization challenges in Brazil, from the implementation of new guidelines in the curricula of health courses to professional practices characterized by the repression of changes and maintenance of the traditional care model, among other crossings. It was possible to conclude that the collaborative practices made possible by multiprofessional residency programs in health contribute to the development of a holistic awareness of each professional who is part of the multidisciplinary resident teams, since they reveal comprehensive knowledge and complement each other in the context of interprofessional education, favoring the integrality of care.